To solve the equation \( 13x - 1 = 19x - 25 \), we start by isolating the variable \( x \).
- First, we can move all terms involving \( x \) to one side of the equation. We can do this by subtracting \( 13x \) from both sides:
\[ -1 = 19x - 13x - 25 \]
- Simplifying the right side gives:
\[ -1 = 6x - 25 \]
- Next, we want to isolate \( 6x \). We can do this by adding 25 to both sides:
\[ -1 + 25 = 6x \]
\[ 24 = 6x \]
- Now, we divide both sides by 6 to solve for \( x \):
\[ x = \frac{24}{6} = 4 \]
The solution is:
\[ \boxed{4} \]